An Investigation into Information Needs and Information Seeking Behavior of Elementary and Middle School Teachers Teaching Indigenous Courses - Shan-Ju L. Chang (Journal of Library and Information Studies, 2006)
The purpose of this research is to systematically study the information need, seeking, and use behavior of middle school teachers of Taiwan historical resources, and to explore the implications of the findings for digital library system design. This research employs multiple methods, first by qualitative approach followed by quantitative approach. The study investigated elementary and high school teachers, and compared the findings with those of the scholar user group, using literature analysis, deep interview, and questionnaire survey as the methods for data collection, and content analysis, case study, and statistic analysis for data analysis. The results lead to (1) a better understanding of information seeking and use behavior of primary and middle school teachers of Taiwan historical archives; (2) deeper knowledge and empirical data for developing theory on human information behavior of Taiwan local people; (3) identification of important teaching and learning resources on Taiwan and the salient characteristics of those resources; (4) development of information organization guideline for localized digital library and museum systems. (Article content in Chinese with English abstract)